Assessment of medical needs of the Hispanic community in Macon-Bibb County, Georgia - Kim Bélanger-Giguère; Jose Pino; Brad Lian (Georgia Southern University, 2016)
Background: Little is known about the health concerns and issues among the Hispanic community in growing, mid-sized cities, such as Macon, Georgia. Methods: A questionnaire on general health-related issues was given to a sample of 125 Hispanic participants. Results: The top health concerns of the Hispanic community were diabetes, obesity, and dental hygiene; the most common factors preventing Hispanics from receiving medical treatment were the lack of insurance, language barriers, and copayments or deductibles being too high. Conclusions: Lack of higher education and the inability to communicate effectively in English may be manifested as difficulties in finding proper information about where to access insurance and healthcare. Therefore, awareness campaigns, more advertising in Spanish, and perhaps increasing the availability of English lessons may be helpful for this population.